Resurrection of the genus Homalopteroides (Teleostei: Balitoridae) with a redescription of H. modestus (Vinciguerra 1890) - Randall, Zachary S.; Page, Lawrence M. (Zootaxa, 2012)
The genus Homalopteroides Fowler 1905 is resurrected and distinguished from the genus Homaloptera van Hasselt 1823based on a combination of characters including a unique mouth morphology, dorsal-fin origin over pelvic fin,≤60 lateral-line scales, and≤30 predorsal scales. Species included in Homalopteroides are H. wassinkii (Bleeker 1853), H. modestus(Vinciguerra 1890), H. rupicola (Prashad & Mukerji 1929), H. smithi (Hora 1932), H. stephensoni (Hora 1932), H. weberi(Hora 1932), H. tweediei (Herre 1940), H. indochinensis (Silas 1953), H. nebulosus (Alfred 1969), H. yuwonoi (Kottelat1998), and possibly H. manipurensis (Arunkumar 1999). Homalopteroides modestus (Vinciguerra 1890) is a poorlyknown species that was originally described from the Meekalan and Meetan rivers of southern Myanmar. It occurs in theSalween, Mae Khlong, and Tenasserim basins, and can be distinguished from all other species of Homalopteroides by thecombination of caudal-fin pattern (black proximal and distal bars, median blotch), 15 pectoral-fin rays, pectoral-fin lengthgreater than head length, 5½–6½ scales above and 5–6 scales below the lateral line (to the pelvic fin), 39–44 total lateral-line pores, no axillary pelvic-fin lobe, pelvic fin not reaching anus, orbital length less than interorbital width in adult, and maxillary barbel reaching to or slightly past the anterior orbital rim.